Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Pemilihan Karir Menjadi Auditor (Studi Empiris Pada Mahasiswa Akuntansi Perpajakan Politeknik Caltex Riau) - Yuliantoro, Heri R; Nurmalasari, Dini; Putri Radha (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The purpose of this study is to ascertain how accounting students' interest in a career as auditors is influenced by societal values, the workplace, financial incentives, job market factors, and personality. The subjects of this study are Caltex Riau Polytechnic students enrolled in the tax accounting study program. 201 Caltex Riau Polytechnic tax accounting study program students made up the research's population. This study's sample consisted of 66 students from tax accounting education programs in their 20th and 21st generations. By using Likert scale-based surveys to gather data, this study employs quantitative approaches. Primary data was employed as the data source for this study. Descriptive statistical analysis, data quality testing, traditional assumption testing, and hypothesis testing are the data analysis methods employed in this study. SPSS 23 is the media or analytical tool utilized in this study. According to the study's findings, the factors of social values, the workplace culture, and financial incentives significantly and negatively affect accounting students' interest in pursuing a career as auditors, whereas personality traits and job market considerations significantly and favorably influence this interest.